Analysis of the coupled dynamic response of an offshore floating multi-purpose platform for the Blue Economy. (1st December 2020) - Li, Liang; Ruzzo, Carlo; Collu, Maurizio; Gao, Yan; Failla, Giuseppe; Arena, Felice
Abstract: A multi-purpose platform is an offshore system designed to serve the purposes of more than one offshore industry. Within the context of "The Blue Growth Farm" project, an innovative multi-purpose configuration, comprising a wind turbine, wave energy converters, and an internal pool to accommodate aquaculture fish cages, has been proposed. The present work proposes a framework to assess the coupled dynamic response of the multi-purpose platform in realistic environmental conditions. A simplified parametric analysis of the structure is first carried out to propose a preliminary design of the platform. The preliminary design is subsequently investigated through hydro-elastic and aero-hydro-servo-elastic coupled analyses. Modal analysis is performed through a 3D finite-element structural model. It confirms the feasibility of rigid-body hypothesis for the dynamic analysis of the support structure and manifests that the vibration modes of the structure are not excited by wave or wind loads. In order to assess the coupled dynamic responses, an aero-hydro-servo-elastic coupled numerical model is developed. The motion and structural responses in operational and survival states are investigated. A modified mean up-crossing rate method has been employed to assess the ultimate limit state. The results obtained from the present research confirm the technical feasibility of the proposed configuration and provide a reference for further studies on similar concepts. Highlights: A novel offshore multi-purpose platform concept is proposed. The structure design is preliminarily optimized using a parametric analysis model. Hydroelasticity of the preliminary design is investigated. An aero-hydro-servo-elastic coupled model is developed to simulate the coupled dynamic response of the multi-purpose platform.